2021
DOI: 10.1002/cncr.33456
|View full text |Cite
|
Sign up to set email alerts
|

Risk‐adapted starting age of breast cancer screening in women with a family history of ovarian or other cancers: A nationwide cohort study

Abstract: BACKGROUND:There is a lack of evidence-based recommendations for the age at which women with a family history of cancers other than breast cancer should start breast cancer screening. METHODS: Using Swedish family cancer data sets, the authors conducted a nationwide cohort study including 5,099,172 Swedish women born after 1931 (follow-up, 1958-2015). Accounting for calendar time, they calculated the relative risk of breast cancer for women with a family history of a discordant cancer in 1 first-degree relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…To date, studies focused on risk-adapted starting ages of breast cancer screening have been conducted with the Swedish family cancer data sets by Mukama et al 11 , 18 , 28 These authors considered a family history of breast cancer, reproductive profile (eg, age at first live birth and parity), and other family history of cancers separately in their study, which makes it difficult for individuals with more than 1 category of risk factors to decide when to screen.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To date, studies focused on risk-adapted starting ages of breast cancer screening have been conducted with the Swedish family cancer data sets by Mukama et al 11 , 18 , 28 These authors considered a family history of breast cancer, reproductive profile (eg, age at first live birth and parity), and other family history of cancers separately in their study, which makes it difficult for individuals with more than 1 category of risk factors to decide when to screen.…”
Section: Discussionmentioning
confidence: 99%
“…27 Although all of these factors were considered in the China Guideline for the Screening and Early Detection of Female Breast Cancer, 19 the recommended starting age of screening for women at average and increased risk was based on expert opinion and lacked population-based evidence in Chinese women. Evidence of a risk-adapted starting age of screening is needed to determine populations at high risk and promote screening of To date, studies focused on risk-adapted starting ages of breast cancer screening have been conducted with the Swedish family cancer data sets by Mukama et al 11,18,28 These authors considered a family history of breast cancer, reproductive profile (eg, age at first live birth and parity), and other family history of cancers separately in their study, which makes it difficult for individuals with more than 1 category of risk factors to decide when to screen.…”
Section: Sensitivity Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Family history of breast cancer and some other cancers is an established risk factor for being diagnosed with breast cancer. Previous studies suggested that individuals with family history of breast cancer in first-degree relatives were at a 1.8-fold increased risk to be diagnosed with breast cancer, whereas those with family history of ovarian cancer had a moderately increased risk (1.3-fold), and those with family history of stomach, colorectum, pancreas, and lung cancer had slightly increased risk (approximately 1.1-fold) ( 11 , 12 ). However, whether such familial risk differs by ER status is unclear, and risk estimates of ER-specific breast cancers by family history of cancer are currently lacking.…”
mentioning
confidence: 99%